Characterization and Transcriptional Regulation of the 2-Ketogluconate Utilization Operon in Pseudomonas plecoglossicida - Lei Sun; Wenqi Yang; Lulu Li; Daming Wang; Xinyi Zan; Fengjie Cui; Xianghui Qi; Ling Sun; Wenjing Sun (Microorganisms)
Pseudomonas plecoglossicida JUIM01 is an industrial 2-keto-d-gluconate (2KGA)-producing strain. However, its regulation mechanism of 2KGA metabolism remains to be clarified. Among other reported Pseudomonas species, the 2-ketogluconate utilization operon (kgu operon) plays key roles in 2KGA catabolism. In this study, the structural genes of the kgu operon and its promoter in P. plecoglossicida JUIM01 were identified using reverse transcription PCR and lacZ reporter gene fusion. The results showed the kgu operon in P. plecoglossicida was composed of four structural genes: kguE, kguK, kguT, and kguD. The ptxS gene located upstream of kguE was excluded from the kgu operon. Then, the knockout and corresponding complementation strains of kguE, kguK, kguT, and kguD were constructed, respectively, to prove the kgu operon was involved in 2KGA catabolism of P. plecoglossicida. The knockout stains, especially JUIM01ΔkguE, showed potential as industrial production strains for 2KGA. Moreover, the transcriptional regulation mechanism of PtxS on the kgu operon was elucidated using multiple methods. In P. plecoglossicida, the LacI-family transcription regulator PtxS could recognize a 14 bp palindrome (5′-TGAAACCGGTTTCA-3′) within the promoter region of the kgu operon and specifically bind to a 26 bp region where the palindrome was located. As the binding sites overlapped with the transcription start site of the kgu operon, the binding of PtxS possibly hindered the binding of RNA polymerase, thus repressing the transcription of the kgu operon and further regulating 2KGA catabolism. 2KGA bound to PtxS as an effector to dissociate it from the kgu operon promoter region, so as to relieve the transcription repression. The results will provide strategies for improving the product accumulation in 2KGA industrial production and theoretical bases for the construction of a Pseudomonas chassis.